A method for preparing a self-repairing anti-corrosion coating and combining it with cathodic protection

By growing Prussian blue-like MOF on graphene oxide and loading nano ceria, PBA-GO@CeO2 nanofiller was prepared, and composite coating was added to epoxy resin, and used in combination with cathodic protection, the existing self-healing anticorrosion coating was solved. High adhesion, strong impedance mode value and self-healing ability were achieved, and stronger corrosion protection performance was provided.

CN118909510BActive Publication Date: 2025-03-28OCEAN UNIV OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411150215.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-03-28
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing self-healing anticorrosion coatings have unstable performance in severe marine environments, low adhesion, and local corrosion occurs after coupling between the anode and cathode regions.

Method used

PBA-GO@CeO2 nanofiller was prepared by growing Prussian blue-like MOF on graphene oxide and loading nano ceria, adding it to epoxy resin to prepare a composite coating, and used in combination with cathodic protection to improve the protective effect.

Benefits of technology

The coating is achieved with high adhesion, strong impedance mode value and self-repair ability, effectively suppressing the peeling and failure of the coating and providing stronger corrosion protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909510B_ABST
    Figure CN118909510B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of coating preparation and corrosion protection, and specifically discloses a method for preparing a self-repairing anti-corrosion coating and a method for combined protection with cathodic protection. The self-repairing anti-corrosion coating comprises the following components in parts by weight: a. 95 to 100 parts of epoxy resin; b. 0.5 to 2 parts of modified two-dimensional nanofiller; c. additives. After the coating is prepared, different cathodic protection potentials are applied to the coating to further improve the protection effect. The self-repairing anti-corrosion coating has the characteristics of strong adhesion, high and low frequency impedance modulus values, etc. It has a certain self-repairing ability when the coating is damaged. When used in combination with cathodic protection, the protective effect of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating preparation and corrosion protection, and specifically relates to a method for preparing a self-repairing anti-corrosion coating and combining it with a cathode protection coating. Background Art

[0002] During the service life of marine engineering equipment, due to the harsh marine environment medium (C l - , S 2- ) and the influence of mechanical external forces often lead to serious corrosion failure problems, resulting in a decrease in the service life of equipment and even safety risks. Among the many metal anti-corrosion strategies, the use of surface coating protection is the most common, economical and effective method.

[0003] Filler is one of the most commonly used ingredients in organic coating systems. Fillers with anti-corrosion properties are crucial to improving the corrosion resistance of coatings. By adding nanofillers with higher specific surface area and smaller particle size to the coating for filler modification, it can play a better barrier and shielding role against corrosive media, thereby improving the corrosion protection performance of the coating to a certain extent.

[0004] Graphene oxide (GO) is the oxide of graphene. The oxidation of graphene surface provides graphene with more surface active sites and a larger specific surface area. At the same time, as a graphene-based two-dimensional material, graphene oxide also has an excellent labyrinth barrier effect, so adding it to the coating will make the coating have a better long-term corrosion protection effect.

[0005] The invention patent with application number CN202211629888.6 discloses a method for preparing a GO / Ce-MOF@PDA / PU superhydrophobic self-healing anti-corrosion coating. First, a dual-coordinated MOF is grown in situ on graphene oxide, and then polydopamine is introduced to chemically modify the graphene oxide, and then a low surface energy reagent is used to reduce the surface energy of the composite, and finally mixed with polyurethane and sprayed to obtain a coating; although PU (polyurethane) has certain flexibility, its mechanical strength and wear resistance are generally low, which affects the long-term durability of the coating, and the combination of PDA (polydopamine) and PU is relatively poor in weather resistance and has low adhesion, resulting in insufficient stability and durability of the coating performance under extreme environments.

[0006] Moreover, in the harsh corrosive environment of the ocean, the coating will inevitably be affected by the scouring of seawater, erosion of mud and sand, alternating dry and wet conditions, and the attachment of marine organisms, resulting in significant damage and peeling. The exposed part of the coating will become the anode area, coupling with the strong cathode area, causing severe local corrosion of the metal. Summary of the invention

[0007] The purpose of the present invention is to seek to design a self-repairing anti-corrosion coating preparation and a corrosion protection method for use in conjunction with cathodic protection. This self-repairing anti-corrosion coating has the characteristics of strong adhesion, high and low frequency impedance modulus, etc., and has a certain self-repairing ability when the coating is damaged. When used in conjunction with cathodic protection, it can effectively inhibit the peeling and failure of the anti-corrosion coating. It can provide effective corrosion protection for marine engineering equipment such as ships, offshore platforms, and offshore wind power.

[0008] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0009] A method for preparing a self-repairing anti-corrosion coating, characterized in that it comprises the following components in parts by weight:

[0010] a. 95-100 parts of epoxy resin;

[0011] b. 0.5 to 2 parts of modified two-dimensional nanofiller;

[0012] c. Additives;

[0013] The component b is obtained by the following preparation method:

[0014] The graphene oxide is modified by using a Prussian blue (PBA) type MOF material to prepare PBA-GO@CeO2 nanofiller, which specifically includes the following steps:

[0015] S101, dissolving graphene oxide, sodium citrate dihydrate, and cobalt acetate tetrahydrate in deionized water, and performing ultrasonic treatment to obtain solution A;

[0016] S102, dissolving potassium ferrocyanide and nano-cerium dioxide in deionized water, and applying magnetic stirring to obtain solution B;

[0017] S103, pouring solution A into solution B, stirring magnetically and then heating for reaction;

[0018] S104, cooling the mixed solution to room temperature, and obtaining PBA-GO@CeO2 nanofiller by centrifugal washing and vacuum drying;

[0019] Furthermore, in step S101, the mass ratio of graphene oxide, deionized water, cobalt acetate tetrahydrate, and sodium citrate dihydrate is 0.5-1.5:3.5*10 3 ~4.5*10 3 :12~17:12~17.

[0020] Furthermore, in step S102, the mass ratio of potassium ferrocyanide, deionized water, and nano-cerium dioxide is 0.5-1.5:5*10 2 ~7*10 2 :0.2~0.6.

[0021] Furthermore, in step S103, the specific steps include: pouring the solution A into the solution B, continuing magnetic stirring for 15 minutes, and then using a constant temperature water bath to heat the mixed solution at 80° C. for 6 hours.

[0022] Furthermore, in step S104, the specific steps include: cooling the mixed solution to room temperature, centrifuging and washing with deionized water and anhydrous ethanol, the centrifuge speed is 8000r / min, and the collected solid is placed in a 60°C vacuum drying oven and dried for 24 hours to obtain gray PBA-GO@CeO2 powder.

[0023] Furthermore, the method for preparing the self-repairing anti-corrosion coating comprises the following steps:

[0024] S201, mixing the PBA-GO@CeO2 nanofiller and the epoxy resin matrix in a certain proportion, and uniformly dispersing the powder by a ball mill;

[0025] S202, adding an additive, removing bubbles by ultrasonic treatment, and then evenly applying the additive to the metal surface with an applicator to form a coating A;

[0026] S203. Dry the coating sample at room temperature for 96 hours, and then place it in a 60°C vacuum oven to continue drying for 6 hours to obtain a PBA-GO@CeO2 / EP composite coating.

[0027] Among them, the additives include curing agents, solvents and defoaming agents.

[0028] Further, in step S201, the specific steps include: adding 0.5 to 2 parts by weight of PBA-GO@CeO2 to 95 to 100 parts by weight of epoxy resin matrix, and using a ball mill to evenly disperse the filler into the resin matrix, the ball milling speed is 360 r / min, and the ball milling time is 12 hours;

[0029] In step S202, the specific steps include: adding a curing agent and a solvent to the mixture after the ball milling is completed, continuously stirring until the resin is dissolved into a liquid state, adding 1wt.% of a defoaming agent, and using an ultrasonic cleaner to ultrasonically clean the coating for 30 minutes to remove bubbles inside and on the surface of the coating. After no obvious bubbles can be observed with the naked eye, the coating is evenly applied to the metal surface using a coater, which is recorded as coating A.

[0030] Furthermore, the mass ratio of the mixture, the curing agent and the solvent is 4:2:1.

[0031] Furthermore, the curing agent is a polyamide resin, and the solvent is a mixed solution of xylene and n-butanol in a mass ratio of 7:3.

[0032] As a further optimization scheme of the present invention, the present invention also provides a combined protection method of a self-repairing anti-corrosion coating and cathodic protection. The self-repairing coating is prepared by the above-mentioned preparation method, and the specific steps include: applying a cathodic protection potential to the damaged coating, and the cathodic protection time is 60 days.

[0033] The beneficial effects of the present invention are as follows: the present invention modifies graphene oxide with good shielding properties by using a Prussian blue (PBA)-like MOF material, and loads nano-cerium dioxide on its surface to prepare PBA-GO@CeO2 nanofiller, and the PBA-GO@CeO2 / EP composite coating prepared by adding it to an epoxy coating (EP) has the characteristics of strong adhesion, high and low frequency impedance modulus, etc., and has a certain self-repairing ability when the coating is damaged. After being used in combination with cathodic protection, the protective effect of the coating is further improved, and the peeling and failure of the anti-corrosion coating can be effectively inhibited. It can provide effective corrosion protection for marine engineering equipment such as ships, offshore platforms, and offshore wind power. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is the infrared spectra of GO, PBA-GO and PBA-GO@CeO2 of the present invention;

[0035] Figure 2 are XRD patterns of GO, PBA-GO and PBA-GO@CeO2 of the present invention;

[0036] Figure 3 It is the SEM photos of GO and PBA-GO@CeO2 of the present invention and the element distribution spectrum of PBA-GO@CeO2;

[0037] Figure 4 is a graph showing adhesion test results of different composite coatings of the present invention;

[0038] Figure 5 are EIS spectra of different composite coatings of the present invention;

[0039] Figure 6 is the low frequency impedance modulus of different composite coatings of the present invention;

[0040] Figure 7 These are optical photographs of the damaged area of ​​the coating after 60 days under different cathodic protection potentials of the present invention. DETAILED DESCRIPTION

[0041] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0042] Example 1

[0043] A method for preparing a self-repairing anti-corrosion coating comprises the following steps:

[0044] Weigh 20 mg of graphene oxide using an analytical balance, pour into a clean beaker containing 80 mL of deionized water, and use an ultrasonic cleaner to ultrasonicate the mixed solution for 1 h in an ice bath to completely dissolve the graphene oxide; weigh 300 mg of cobalt acetate tetrahydrate and 294 mg of sodium citrate dihydrate using an analytical balance, pour into the mixed solution containing graphene oxide, and continue to ultrasonicate the mixed solution for 1 h using an ultrasonic cleaner to obtain a uniformly dispersed solution, which is recorded as solution A;

[0045] Weigh 264 mg of potassium ferrocyanide with an analytical balance and pour it into another clean beaker filled with 120 mL of deionized water. Stir the mixed solution with a magnetic stirrer for 20 min at a speed of 1000 r / min. During the stirring process, weigh 0.1 g of nano-cerium dioxide with an analytical balance and pour it into the mixed solution to finally obtain a uniformly dispersed solution, which is recorded as solution B.

[0046] Solution A was poured into solution B and magnetic stirring was continued for 15 min. The mixed solution was then heated at 80 °C for 6 h in a constant temperature water bath. The solution turned pink, indicating the synthesis of the PBA-type MOF structure.

[0047] After the solution was cooled to room temperature, it was washed by centrifugation with deionized water and anhydrous ethanol for 6 times at a centrifuge speed of 8000 r / min. The solid was collected and placed in a vacuum drying oven at 60°C for 24 h to obtain a gray PBA-GO@CeO2 powder.

[0048] 1 part by weight of PBA-GO@CeO2 was added to 100 parts by weight of epoxy resin matrix, and the filler was evenly dispersed into the resin matrix using a ball mill. The ball milling speed was 360 r / min and the ball milling time was 12 h.

[0049] After ball milling, polyamide resin and a mixed solution of xylene and n-butanol in a mass ratio of 7:3 were added to the mixture, and stirring was continued until the resin dissolved into a liquid state. 1wt.% defoamer was added, and an ultrasonic cleaner was used for 30 minutes to remove bubbles inside and on the surface of the coating. After no obvious bubbles were observed with the naked eye, the epoxy resin was evenly coated on the metal surface using a coater, which was recorded as coating A. The coating sample was dried at room temperature for 96 hours, and then placed in a vacuum oven at 60°C for further drying for 6 hours. After the coating was completely cured, the coating was subjected to electrochemical and mechanical tests to obtain a 1% PBA-GO@CeO2 / EP composite coating.

[0050] Example 2

[0051] A method for preparing a self-repairing anti-corrosion coating comprises the following steps:

[0052] Weigh 20 mg of graphene oxide using an analytical balance, pour into a clean beaker containing 80 mL of deionized water, and use an ultrasonic cleaner to ultrasonicate the mixed solution for 1 h in an ice bath to completely dissolve the graphene oxide; weigh 300 mg of cobalt acetate tetrahydrate and 294 mg of sodium citrate dihydrate using an analytical balance, pour into the mixed solution containing graphene oxide, and continue to ultrasonicate the mixed solution for 1 h using an ultrasonic cleaner to obtain a uniformly dispersed solution, which is recorded as solution A;

[0053] Weigh 264 mg of potassium ferrocyanide with an analytical balance and pour it into another clean beaker filled with 120 mL of deionized water. Stir the mixed solution with a magnetic stirrer for 20 min at a speed of 1000 r / min. During the stirring process, weigh 0.1 g of nano-cerium dioxide with an analytical balance and pour it into the mixed solution to finally obtain a uniformly dispersed solution, which is recorded as solution B.

[0054] Solution A was poured into solution B and magnetic stirring was continued for 15 min. The mixed solution was then heated at 80 °C for 6 h in a constant temperature water bath. The solution turned pink, indicating the synthesis of the PBA-type MOF structure.

[0055] After the solution was cooled to room temperature, it was washed by centrifugation with deionized water and anhydrous ethanol for 6 times at a centrifuge speed of 8000 r / min. The solid was collected and placed in a vacuum drying oven at 60°C for 24 h to obtain a gray PBA-GO@CeO2 powder.

[0056] 0.5 parts by weight of PBA-GO@CeO2 was added to 100 parts by weight of epoxy resin matrix, and the filler was evenly dispersed into the resin matrix using a ball mill. The ball milling speed was 360 r / min and the ball milling time was 12 h.

[0057] After ball milling, polyamide resin and a mixed solution of xylene and n-butanol in a mass ratio of 7:3 were added to the mixture, and stirring was continued until the resin dissolved into a liquid state. 1wt.% defoamer was added, and an ultrasonic cleaner was used for 30 minutes to remove bubbles inside and on the surface of the coating. After no obvious bubbles were observed with the naked eye, the epoxy resin was evenly coated on the metal surface using a coater, which was recorded as coating A. The coating sample was dried at room temperature for 96 hours, and then placed in a vacuum oven at 60°C for further drying for 6 hours. After the coating was completely cured, the coating was subjected to electrochemical and mechanical tests to obtain a 0.5% PBA-GO@CeO2 / EP composite coating.

[0058] Example 3

[0059] A method for preparing a self-repairing anti-corrosion coating comprises the following steps:

[0060] Weigh 20 mg of graphene oxide using an analytical balance, pour into a clean beaker containing 80 mL of deionized water, and use an ultrasonic cleaner to ultrasonicate the mixed solution for 1 h in an ice bath to completely dissolve the graphene oxide; weigh 300 mg of cobalt acetate tetrahydrate and 294 mg of sodium citrate dihydrate using an analytical balance, pour into the mixed solution containing graphene oxide, and continue to ultrasonicate the mixed solution for 1 h using an ultrasonic cleaner to obtain a uniformly dispersed solution, which is recorded as solution A;

[0061] Weigh 264 mg of potassium ferrocyanide with an analytical balance and pour it into another clean beaker filled with 120 mL of deionized water. Stir the mixed solution with a magnetic stirrer for 20 min at a speed of 1000 r / min. During the stirring process, weigh 0.1 g of nano-cerium dioxide with an analytical balance and pour it into the mixed solution to finally obtain a uniformly dispersed solution, which is recorded as solution B.

[0062] Solution A was poured into solution B and magnetic stirring was continued for 15 min. The mixed solution was then heated at 80 °C for 6 h in a constant temperature water bath. The solution turned pink, indicating the synthesis of the PBA-type MOF structure.

[0063] After the solution was cooled to room temperature, it was washed by centrifugation with deionized water and anhydrous ethanol for 6 times at a centrifuge speed of 8000 r / min. The solid was collected and placed in a vacuum drying oven at 60°C for 24 h to obtain a gray PBA-GO@CeO2 powder.

[0064] 2 parts by weight of PBA-GO@CeO2 were added to 100 parts by weight of epoxy resin matrix, and the filler was evenly dispersed into the resin matrix using a ball mill. The ball milling speed was 360 r / min and the ball milling time was 12 h.

[0065] After ball milling, polyamide resin and a mixed solution of xylene and n-butanol in a mass ratio of 7:3 were added to the mixture, and stirring was continued until the resin dissolved into a liquid state. 1wt.% defoamer was added, and an ultrasonic cleaner was used for 30 minutes to remove bubbles inside and on the surface of the coating. After no obvious bubbles were observed with the naked eye, the epoxy resin was evenly coated on the metal surface using a coater, which was recorded as coating A. The coating sample was dried at room temperature for 96 hours, and then placed in a vacuum oven at 60°C for further drying for 6 hours. After the coating was completely cured, the coating was subjected to electrochemical and mechanical tests to obtain a 2% PBA-GO@CeO2 / EP composite coating.

[0066] Example 4

[0067] A cathodic protection potential of -1.0 V was applied to the damaged coating in Example 1, and the cathodic protection time was 60 days.

[0068] Example 5

[0069] The difference from Example 4 is that a cathode protection potential of -1.2 V is applied.

[0070] The following table shows some of the component parameters used in Examples 1-5:

[0071] Example <![CDATA[PBA-GO@CeO2]]> Epoxy resin Potential value (V) 1 1 100 / 2 0.5 100 / 3 2 100 / 4 1 100 -1.0 5 1 100 -1.2

[0072] Infrared spectroscopy analysis experiment

[0073] Infrared spectroscopy analysis experiments were performed on GO (unmodified graphene oxide), PBA-GO (PBA-GO nanofiller modified by MOF in the present application), and PBA-GO@CeO2 (PBA-GO@CeO2 nanofiller prepared by loading nano-cerium dioxide in the present application). Figure 1 Shown: For the FT IR spectrum of GO, 1736 cm -1 、1622cm -1 、1227cm -1 and 1060cm -1 The characteristic peaks at 1736 cm-1 correspond to the stretching vibration peak of C=O in the carboxyl group, the stretching vibration peak of aromatic C=C, the OH deformation vibration peak of the epoxy group, and the stretching vibration peak of COC. For the PBA-GO material, the carboxyl group, epoxy group, and COC bond are at 1736 cm-1, respectively. -1 1622cm -1 and 1060cm -1 The characteristic peaks of C=O, OH and COC at 2083cm -1 The new peak at 2970cm corresponds to the stretching vibration peak of C≡N bond. The appearance of the new peak successfully confirms the composite of PBA and GO. -1 and 1560cm -1 The characteristic peaks at correspond to the vibration peaks of CeO2 and the U3 vibration mode of carbonate ions, confirming the successful loading of CeO2 nanoparticles.

[0074] X-ray diffraction test

[0075] X-ray diffraction tests were performed on GO (unmodified graphene oxide), PBA-GO (PBA-GO nanofiller modified by MOF in the present application), and PBA-GO@CeO2 (PBA-GO@CeO2 nanofiller prepared by loading nano-cerium dioxide in the present application). The test results are as follows: Figure 2As shown: The strong diffraction peak of GO at about 10° represents the (002) crystal plane, while the weak diffraction peak at about 42° represents the (100) crystal plane. For PBA-GO and PBA-GO@CeO2 materials, the disappearance of the diffraction peak corresponding to GO in the XRD spectrum is due to the coverage of GO nanosheets by PBA materials, thereby destroying the conventional stacking of GO. There are obvious diffraction peaks at the (200), (220), (400), (420), (422), (440) and (620) crystal planes of the XRD spectrum of PBA-GO, indicating that it has a fairly high degree of crystallinity, which is consistent with the PDF card (JCPDS No.: No.01-075-0038), corresponding to CoFe(CN)6 2- For PBA-GO@CeO2, the (111), (200), (220) and (311) crystal planes of the XRD spectrum correspond to the diffraction peaks of CeO2. At the same time, it can be seen that the diffraction peaks of PBA-GO can be seen in PBA-GO@CeO2, indicating that the loading of CeO2 will not destroy the structure of PBA-GO.

[0076] The pure GO (unmodified graphene oxide) and PBA-GO@CeO2 (PBA-GO@CeO2 nanofiller prepared by loading nano-cerium dioxide in the present application) were observed by electron microscopy and combined with energy spectrum analysis, as shown in FIG. Figure 3 As shown in the figure, (a) is the SEM photo of GO, (b)-(d) are the SEM photos of PBA-GO@CeO2, and (e)-(f) are the element distribution maps of PBA-GO@CeO2. It can be seen from the figure that for pure GO, an obvious wrinkle structure can be observed on the surface; Photo (b) shows that for PBA-GO@CeO2, a large number of particles grow on the surface of the GO sheet; Photo (c) shows that the surface material is further magnified, and the material shows an obvious hollow porous framework structure, which indirectly proves the successful preparation of the PBA material; Photos (e) and (f) respectively show the element mapping results and atomic percentages of the material in Photo (d). It can be seen that the C element is distributed in the entire test area and has the highest content, representing the GO substrate. The distribution positions of the N element, Fe element and Co element correspond to the structure of PBA, and the distribution of the Ce element and part of the O element corresponds to CeO2, indicating that the CeO2 material is loaded on the GO surface. The above results prove the successful synthesis of PBA-GO@CeO2.

[0077] Adhesion test:

[0078] Epoxy coating (without nanofiller), 1% GO composite coating (with unmodified graphene oxide nanofiller), 1% PBA-GO composite coating (with MOF-modified PBA-GO nanofiller), 0.5% PBA-GO@CeO2 / EP composite coating (with PBA-GO@CeO2 nanofiller loaded with nano-cerium oxide), 1% PBA-GO@CeO2 / EP composite coating (with PBA-GO@CeO2 nanofiller loaded with nano-cerium oxide) and 2% PBA-GO@CeO2 / EP composite coating (with PBA-GO@CeO2 nanofiller loaded with nano-cerium oxide) were extracted and subjected to pull-out tests (the pull-out test can be carried out using a pull-out testing machine or other suitable device, as long as it is ensured that a uniform tensile force can be applied and the applied force can be measured. This application does not make any new improvements to the pull-out test, so the specific steps of the experiment are not repeated). The experimental results are as follows: Figure 4 As shown in the figure, (1) represents epoxy coating; (2) represents 1% GO composite coating; (3) represents 1% PBA-GO composite coating; (4) represents 0.5% PBA-GO@CeO2 / EP composite coating; (5) represents 1% PBA-GO@CeO2 / EP composite coating; (6) represents 2% PBA-GO@CeO2 / EP composite coating, dark color represents dry adhesion strength, light color represents wet adhesion strength, Figure 4 It can be seen that the dry adhesion strength and wet adhesion strength of epoxy resin are relatively low. The 1% GO coating has higher adhesion than the pure epoxy coating. After the GO coating is modified by PBA, the adhesion strength is further increased. The 1% PBA-GO@CeO2 / EP composite coating has the highest adhesion. However, excessive addition of filler will affect its dispersibility, thereby reducing the adhesion strength of the interface.

[0079] Electrochemical Impedance Spectroscopy (EIS) Test:

[0080] 1% PBA-GO, 0.5% PBA-GO@CeO2 / EP, 1% PBA-GO@CeO2 / EP and 2% PBA-GO@CeO2 / EP were taken for electrochemical tests. The experimental results are shown in Figure 5As shown in the figure, (a1)-(a3) are the E IS spectra of 1% PBA-GO; (b1)-(b3) are the E IS spectra of 0.5% PBA-GO@CeO2 / EP; (c1)-(c3) are the E IS spectra of 1% PBA-GO@CeO2 / EP; (d1)-(d3) are the E IS spectra of 2% PBA-GO@CeO2 / EP; It can be seen from the test results that the capacitive reactance radius and phase angle curve coverage area values ​​of the 1% PBA-GO composite coating are higher than those of the 1% GO composite coating, and the decrease is smaller within the 60-day period of the test, indicating that the modification of PBA further improves the dispersibility and compatibility of GO, thereby improving the long-term corrosion protection effect of the coating, further illustrating that the 1% PBA-GO@CeO2 / EP composite coating has excellent corrosion resistance;

[0081] like Figure 6 As shown, for 1% PBA-GO@CeO2 / EP composite coating, |Z| 0.01Hz During the soaking period, it gradually increased from 1.48×10 9 Ω·cm 2 Gradually increased to 1.89×10 10 Ω·cm 2 ,After 60 days of immersion, the coating's |Z| 0.01Hz Stable at 1.63×10 10 Ω·cm 2 The above shows that the coating has the best long-term anti-corrosion and self-repairing performance at this time.

[0082] The epoxy coating, 1% PBA-GO composite coating, and 1% PBA-GO@CeO2 / EP composite coating with different cathodic protection potentials were taken respectively, and the coating damage areas after 60 days under different cathodic protection potentials were analyzed and compared. Figure 7 As shown in the figure, (a)-(c) represent optical photographs of epoxy coatings; (d)-(f) represent optical photographs of 1% PBA-GO composite coatings; (g)-(i) represent optical photographs of 1% PBA-GO@CeO2 / EP composite coatings, wherein (a), (d), and (g) are not subjected to cathodic protection; (b), (e), and (h) are subjected to -1.0V cathodic protection potential; (c), (f), and (i) are subjected to -1.2V cathodic protection potential;

[0083] The results show that for the damaged 1% PBA-GO@CeO2 / EP composite coating, its corrosion degree is the lightest under different cathodic protection potentials. After applying a cathodic protection potential of -1.2V, the damaged defect is the smallest, and the white product appearing at the damaged part almost completely covers the damaged defect, indicating that the coating has good self-healing ability, and the combined effect of the PBA-GO@CeO2 / EP composite coating and cathodic over-protection has a good protective effect on the substrate.

[0084] The experiment proved that PBA-GO@CeO2 can be successfully prepared by the solvothermal method of growing PBA-type MOF on GO and loading CeO2, and after immersion in seawater for 60 days, the |Z| of 1% PBA-GO@CeO2 / EP composite coating 0.01Hz Higher than 1.63×10 10 Ω·cm 2 . After the damaged coating was polarized at a cathodic protection potential of -1.2 V for 168 h, |Z| 0.01Hz It reached more than 3 times the initial value, indicating that the 1% PBA-GO@CeO2 / EP composite coating has the highest anti-corrosion self-repair performance, and applying a cathodic protection potential of -1.2V to the damaged coating can further improve the protection effect. The results have a certain guiding significance for the combined effect of cathodic protection and organic coating in engineering.

[0085] It should be noted that Prussian blue (PBA)-type MOF materials are metal ion compounds with Fe and Co diatoms as metal ligands. Compared with single-atom MOF materials, the coordination of dimetallic ions can form more hydroxides. At the same time, PBA materials are generally stable in strong alkaline environments and are easy to decompose, which provides the possibility for the preparation of self-healing coatings under cathodic protection.

[0086] Cerium dioxide (CeO2) is a nanofiller with corrosion inhibition effect and is stable in alkaline environment. It can also play a self-repairing role when added to the coating. Therefore, the self-repairing anti-corrosion coating uses a hydrothermal method to grow PBA-type MOF on GO nanosheets and load nano-CeO2 to prepare PBA-GO@CeO2 and PBA-GO@CeO2 nanofiller modified epoxy coatings;

[0087] Cathodic protection can be divided into sacrificial anode cathodic protection and impressed current cathodic protection. Impressed current cathodic protection is to continuously apply cathodic current to the metal surface through an external power source, so that the surface potential of the protected metal structure is reduced to become the cathode in the environment, thereby preventing its surface from losing electrons and undergoing redox reactions.

[0088] The combined effect of cathodic protection and organic coating will play a complementary role. On the one hand, the complete organic coating has good chemical medium shielding properties, which can play a major protective role in the early stage of service and reduce the cost of cathodic protection. On the other hand, after the organic coating fails in the middle and late stages of service, the current provided by cathodic protection can continue to provide protection for the metal. Studies have shown that proper cathodic protection can slow down the consumption of corrosion-resistant pigments in the coating and improve the water resistance and wet adhesion of the coating. Therefore, the combined effect of organic coating and cathodic protection has important engineering value.

[0089] In addition, the testing and experimental methods adopted in the present invention are all existing technologies, and no further improvements are made to them in this application, so the detailed testing steps are not recorded.

[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a self-repairing anti-corrosion coating, characterized in that: The composition comprises the following components in parts by weight: a. 95-100 parts of epoxy resin; b. 0.5 to 2 parts of modified two-dimensional nanofiller; c. Additives; The component b is obtained by the following preparation method: The PBA-GO@CeO2 nanofiller is prepared by modifying graphene oxide with a Prussian blue-like PBA type MOF material, which specifically includes the following steps: S101, dissolving graphene oxide, sodium citrate dihydrate, and cobalt acetate tetrahydrate in deionized water, and performing ultrasonic treatment to obtain solution A; S102, dissolving potassium ferrocyanide and nano-cerium dioxide in deionized water, and applying magnetic stirring to obtain solution B; S103, pouring solution A into solution B, stirring magnetically and then heating for reaction; S104, cooling the mixed solution to room temperature, and obtaining PBA-GO@CeO2 nanofiller through centrifugal washing and vacuum drying.

2. A method for preparing a self-repairing anti-corrosion coating according to claim 1, characterized in that: In step S101, the mass ratio of graphene oxide, deionized water, cobalt acetate tetrahydrate, and sodium citrate dihydrate is 0.5-1.5:3.5*10 3 ~4.5*10 3 :12~17:12~17.

3. A method for preparing a self-repairing anti-corrosion coating according to claim 2, characterized in that: In step S102, the mass ratio of potassium ferrocyanide, deionized water, and nano-cerium dioxide is 0.5-1.5:5*10 2 ~7*10 2 :0.2~0.

6.

4. A method for preparing a self-repairing anti-corrosion coating according to claim 3, characterized in that: In step S103, the specific steps include: pouring the solution A into the solution B, continuing magnetic stirring for 15 minutes, and then using a constant temperature water bath to heat the mixed solution at 80° C. for 6 hours to obtain a pink PBA-MOF structure.

5. A method for preparing a self-repairing anti-corrosion coating according to claim 4, characterized in that: In step S104, the specific steps include: cooling the mixed solution to room temperature, washing it by centrifugation with deionized water and anhydrous ethanol, the centrifuge speed is 8000r / min, and the collected solid is placed in a vacuum drying oven at 60°C and dried for 24h.

6. The method for preparing a self-repairing anti-corrosion coating according to claim 1, characterized in that: The method for preparing the self-repairing anti-corrosion coating comprises the following steps: S201, mixing the PBA-GO@CeO2 nanofiller and the epoxy resin matrix in a certain proportion, and uniformly dispersing the powder by a ball mill; S202, adding an additive, removing bubbles by ultrasonic treatment, and then evenly applying the additive to the metal surface with an applicator to form a coating A; S203, drying the coating sample at room temperature for 96 hours, and then placing it in a vacuum oven at 60°C for further drying for 6 hours to obtain a PBA-GO@CeO2 / EP composite coating; Among them, the additives include curing agents, solvents and defoaming agents.

7. A method for preparing a self-repairing anti-corrosion coating according to claim 6, characterized in that: In step S201, the specific steps include: adding 0.5-2 parts by weight of PBA-GO@CeO2 to 95-100 parts by weight of epoxy resin matrix, and using a ball mill to evenly disperse the filler into the resin matrix, the ball milling speed is 360r / min, and the ball milling time is 12h; In step S202, the specific steps include: adding a curing agent and a solvent to the mixture after the ball milling is completed, continuously stirring until the resin is dissolved into a liquid state, adding 1wt.% of a defoaming agent, and using an ultrasonic cleaner to ultrasonically clean the coating for 30 minutes to remove bubbles inside and on the surface of the coating. After no obvious bubbles can be observed with the naked eye, use a coater to evenly apply it to the metal surface, which is recorded as coating A.

8. A method for preparing a self-repairing anti-corrosion coating according to claim 7, characterized in that: The mass ratio of the mixture, the curing agent and the solvent is 4:2:

1.

9. A method for preparing a self-repairing anti-corrosion coating according to claim 8, characterized in that: The curing agent is polyamide resin, and the solvent is a mixed solution of xylene and n-butanol in a mass ratio of 7:

3.

10. A self-repairing anti-corrosion coating and cathodic protection combined protection method, characterized in that: The self-repairing anti-corrosion coating is prepared by the preparation method described in any one of claims 1 to 9, and the specific steps include: applying a cathodic protection potential to the damaged coating, and the cathodic protection time is 60 days.

Citation Information

Patent Citations

  • A method for preparing a GO / Ce-MOF@PDA / PU superhydrophobic self-healing anti-corrosion coating

    CN115678411B

  • Fluorinated graphene / CeO2 nano-composite modified anti-corrosive coating and preparation method thereof

    CN112175477A

  • Corrosion inhibitor supported GONR (at) BTA-MOFs composite material, preparation method thereof and composite epoxy coating

    CN118290824A